The Development of Assessment Instrument Based on Wordwall to Measure Process Science Skills for Environmental Pollution - Wahyuni, Sri; Ridlo, Zainur Rasyid; Bachtiar, Rayendra Wahyu; Abdillah, Mohammad Hilmy; Enriquez, Alexis Arizabal (IJIS Edu : Indonesian Journal of Integrated Science Education, 2024)
This study aims to determine the validity, practicality, and effectiveness of an assessment instruments based on Wordwall in measuring students' science process skills of junior high school science learning in environmental pollution materials. This research is a type of development research (Research and Development) that refers to the procedure of the Borg and Gall development model which has stages including research and information collecting, planning, develop the preliminary form of the product, product design validation, main product revisions, main field testing, operational product revision, operational field testing, final product revision. The subject of the study was a grade VII student of SMPN 2 Ajung, Jember. This study used instruments in the form of validation sheets, practicality sheets, student questionnaire sheets, and science process skills tests. Data analysis techniques used in research consist of validity test analysis, practicality test analysis, and effectiveness test analysis. The results showed that out of 20 multiple-choice questions developed from aspects of material, construction, and language based on the assessment of 3 validators were declared very valid and worthy of use without revision. The twenty multiple-choice questions tested have valid question item validity. The assessment instrument has a reliability value of 0.612. The difficulty level analysis obtained 5 easy criteria questions, 14 medium criteria questions, and 1 difficult criteria question. The effectiveness of the assessment instrument obtained the average results of students' science process skills of 55%, including the sufficient category and student response questionnaires of 81%, so they were declared very good.